KERAGAMAN KEYAKINAN SEBUAH TANTANGAN DAN HARAPAN BAGI KERUKUNAN BERAGAMA (STUDI PEMIKIRAN TH SUMARTANA TENTANG KERAGAMAN KEYAKINAN) - Nugroho Nugroho (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2016)
Intensive conflicts occur when it enters an era of globalization. Sumartana, the Catholic pastor of Jogjakarta, giving the idea that it needs for a new approach of looking at religion in order to prevent the religious conflict. According to Sumartana , all Humans have